Micro Finance and Women Empowerment: A study on Self-Help Groups with special reference to Ramanagar District, Karnataka - N. S, Navyashree; Mani, Suresh (Journal of Neonatal Surgery, 2025)
The paper explores the highlights and functioning of Micro finance through Self Help Groups in Karnataka. The objective of the study is to examine the loan accessibility with indigenous bankers and formal credit bankers for women and also focuses on grant assistance taken from NABARD over a decade. The data reveals that 2 villages namely Chikkanahalli and Sugganahalli were predominately access loan through money lenders and friends rather than formal financial inclusion. The paper also highlights the women participation in Self Help groups pertaining to bank linkages and access of credit has been tremendous moving in a positive urge. It also tells that women participation in economic activities helps in decision making but lacks training, education market access and delayed loan processing. There is a need for market linkages, loan, training facilities needed for the essential women empowerment. The paper concludes that micro finance plays a pivotal role in women empowerment through SHG’s but the challenge of financial inclusion and economic participation remain unchanged.